Case Report: Cystic fibrosis transmembrane conductance regulator gene heterozygous variation presenting with abdominal pain and hepatopancreatic lesions in a child - Lu, Xiu; Ning, Lidong; Zhen, Hong; Liang, Ming; Han, Yulan; Wei, Hongyan; Zeng, Lingdong; Wei, Lihong; Tan, Liqin (Frontiers in Pediatrics, 2026)
BackgroundCystic fibrosis (CF) is an autosomal recessive disorder caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene, leading to multi-system involvement.Case reportA 4-year-old girl presented with a 2-day history of abdominal pain. Clinical manifestations included recurrent epigastric pain and vomiting. Physical examination revealed abdominal distension, mild periumbilical tenderness, and hepatomegaly (liver palpable 4 cm below the right costal margin). Laboratory tests showed elevated pancreatic enzymes: serum amylase 607 U/L, lipase 634 U/L, and pancreatic amylase 252 U/L (all >3 times the upper limit of normal). Abdominal ultrasound demonstrated diffuse hepatic lesions and uneven echogenicity in pancreatic parenchyma. Computed tomography revealed chronic liver disease changes, possible cirrhosis and a slightly enlarged spleen. Hepatobiliary histopathological biopsy indicated biliary obstruction. Whole-exome sequencing identified CFTR allele variants c.3139G > T (paternal source) and c.1409T > A (maternal source). Comparative analysis with the existing literature verified that the G > T mutation at chromosome 7 (chr7):117250723 was previously unreported. Treatment with octreotide, omeprazole, and pancreatic enzyme replacement therapy led to symptom resolution. At follow-up, her condition remained stable: height=109 cm (10th to 25th percentile), weight=18.8 kg (25th to 50th percentile) and stable condition.ConclusionThe clinical manifestations of CF are diverse, and digestive tract symptoms are common; therefore, early identification and diagnosis are required. As chr7: 117250723 G > T may be a pathogenic gene, long-term follow-up is needed.